Citizenship studies - Mitchell, Mike (Dynamic learning, 2016)
Association for Citizenship Teaching Quality Mark resource. Be inspired to take an active role in citizenship and society by working through the skills-based activities and exam support in this textbook; designed by the market leading Citizenship publisher to help you fulfill your potential under the 2016 AQA GCSE (9-1) Citizenship Studies specification.- Build and review your knowledge and understanding through discussion point questions, review questions and learning review points.- Understand the key issues and concepts you need to know using clear, detailed explanations and definitions of key terms supported by real-life case studies that bring topics to life.- Learn and practise the research, analytical, interpretative and evaluative skills required for GCSE Citizenship Studies with a variety of engaging activities.- Extend your learning and research topics further with links to relevant websites.- Feel confident preparing for your exams with assessment guidance, useful advice on writing exam answers and practice questions on every topic